Predictive and prognostic value of circulating tumor cell detection in lung cancer: A clinician's perspective. Issue 2 (February 2015) - Tognela, Annette; Spring, Kevin J.; Becker, Therese; Caixeiro, Nicole J.; Bray, Victoria J.; Yip, Po Yee; Chua, Wei; Lim, Stephanie H.; de Souza, Paul
Abstract There is increasing evidence for the use of circulating tumor cells (CTCs) as a "liquid biopsy" for early detection of lung cancer recurrence, prognosticating disease and monitoring treatment response. Further, CTC molecular analysis and interrogation of single cells hold significant potential in providing insights into tumor biology and the metastatic process. Ongoing research will likely see the translation of CTCs as a prognostic and predictive biomarker in both small cell, and non-small cell, lung cancer to routine clinical practice.